Congruency of colour associations to urban soundscapes, restaurants, and electroacoustic soundscape compostions - Lindborg, PerMagnus (2015)
Soundscapes are the auditory parts of multimodal environments (physical or virtual). We propose that while they may have differing degree of design intent: from non-designed (e.g. pristine, natural, urban areas), via semi-designed (servicescapes, restaurants), to fully designed (film, games, concert music), people approach them with similar listening strategies (Tuuri & Eerola 2012). The ecological model of perception explains crossmodal interactions as biological adaptations. A sound from an identified source may elicit a predictable affective response, but an acoustically equivalent but unidentifiable sound might not (Västfjäll 2013). A richer understanding of soundscape perception could be gained by considering visual associations (e.g. Haverkamp 2009, Giannakis & Smith 2001) of different kinds, in addition to semantic scales (e.g. Axelsson et al. 2010).